Hubungan Riwayat Berat Badan Lahir Rendah Dengan Kejadian Stunting Pada Anak Balita Usia 2-5 Tahun Di Puskesmas Bandarharjo Semarang - Amanda Wahyu Afriani; Rita Kartikasari (Jurnal Sains dan Kesehatan, 2026)
Stunting remains a significant nutritional issue because it can impact a child's long-term growth and development. A history of low birth weight (LBW) is suspected to play a role, reflecting the condition of fetal growth during pregnancy. This study aimed to determine the relationship between a history of LBW and the incidence of stunting in children aged 2–5 years at the Bandarharjo Community Health Center in Semarang in 2025. This study used an analytical design with a case-control approach. The study sample consisted of 203 toddlers selected using consecutive sampling. Data were obtained from the KIA book and height measurements based on WHO standards. Analysis was performed using the Chi-Square test and Odds Ratio (OR) calculation. The proportion of LBW was 10.8% and stunting was 31.0%. There was a significant relationship between a history of LBW and the incidence of stunting (p = 0.012). Toddlers with a history of LBW had approximately a threefold greater risk of experiencing stunting compared to toddlers born with normal weight (OR = 3.059). There is a relationship between a history of low LBW and the incidence of stunting in toddlers aged 2-5 years at the Bandarharjo Community Health Center, Semarang in 2025.